Propagation and reflection of diffusionless torsional waves in a sphere. Issue 3 (16th January 2016) - Maffei, S.; Jackson, A.
Abstract: We consider an inviscid and perfectly conducting fluid sphere in rapid rotation and permeated by a background magnetic field. Such a system admits normal modes in the form of torsional oscillations, namely azimuthal motions of cylinders coaxial with the rotation axis. We analyse this system for a particular background magnetic field that provides a new closed form normal mode solution. We derive Wentzel–Kramers–Brillouin–Jeffreys (WKBJ) approximations to the normal modes, and focus particularly on the reflections that take place on the rotation axis and at the equator. We propose a procedure to calculate the reflection coefficients and we discuss the analogy of our findings with well-known seismological results. Our analytical results are tested against numerical calculations and show good agreement.